1994
DOI: 10.1161/01.cir.90.3.1328
|View full text |Cite
|
Sign up to set email alerts
|

Activation of angiotensinogen and angiotensin-converting enzyme gene expression in the left ventricle of senescent rats.

Abstract: BACKGROUND During senescence, the plasma angiotensin II concentration is decreased, but the regulation of intracardiac angiotensin II synthesis has never been investigated. The purpose of this work was to determine the cardiac content of both angiotensinogen (ANG) and angiotensin-converting enzyme (ACE) mRNAs in 24-month-old Wistar rats. METHODS AND RESULTS Total cardiac RNAs and known amounts of ANG and ACE mRNA transcripts, used as standards, were hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 49 publications
2
39
0
5
Order By: Relevance
“…There may be an overt elevation of components of the system, as reported for Ang II in the heart during aging [19], consistent with observations on the intrarenal RAS [14,[16][17][18]. In experimental models, increases in gene expression of angiotensinogen, angiotensin-converting enzyme (ACE), Ang II type 1 (AT 1 ) and Ang II type 2 (AT 2 ) receptors have been identified in hearts from senescent rats, independent of circulating RAS [22,23]. Blockade of the RAS by either ACE inhibition or AT 1 -receptor blockers prevents the increase in urinary Ang II in several studies [14,16].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…There may be an overt elevation of components of the system, as reported for Ang II in the heart during aging [19], consistent with observations on the intrarenal RAS [14,[16][17][18]. In experimental models, increases in gene expression of angiotensinogen, angiotensin-converting enzyme (ACE), Ang II type 1 (AT 1 ) and Ang II type 2 (AT 2 ) receptors have been identified in hearts from senescent rats, independent of circulating RAS [22,23]. Blockade of the RAS by either ACE inhibition or AT 1 -receptor blockers prevents the increase in urinary Ang II in several studies [14,16].…”
supporting
confidence: 86%
“…Hypertension, increases in bodyweight gain, insulin resistance and renal dysfunction are factors contributing to remodeling associated with aging and diastolic heart disease [8]. As mentioned above, increases in cardiac tissue components of the RAS occur in older rats [19,22,23]. Moreover, in patients with left ventricular hypertrophy, subsystemic doses of intracoronary ACE inhibitors improve left ventricular filling, distensibility and regional relaxation [83].…”
Section: Brain Ras Cardiac Aging and Diastolic Dysfunctionmentioning
confidence: 99%
“…14) Similarly, the cardiac amount of AGT and ACE mRNA was increased in the left ventricle of senescent rats, this being more likely to be related to the age-associated changes in arterial compliance. 15) These data collectively indicate that tissue RAS played a vital role in mediating the diverse pathophysiological functions associated with ageing.…”
Section: Involvement Of the Skeletal Renin-angiotensin System In Age-mentioning
confidence: 85%
“…Such a ratio is comparable to that of ACE mRNA, of which the total quantity is Ϸ150-fold lower in the heart than in the lung, one of the main sources of this enzyme. 30 Robert et al 31 reported that aldosterone-induced cardiac fibrosis is independent of blood pressure. In the present study, spironolactone prevented cardiac hypertrophy and fibrosis in both SHRSP and adrenalectomized SHRSP.…”
Section: Discussionmentioning
confidence: 99%